A Proposed Novel Neurovascular Mechanism for Brain Network Dysfunction After Traumatic Injury - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Keith A. Kroma-Wiley; Dani S. Bassett; David F. Meaney (Annals of Biomedical Engineering, 2026)
Current research in predicting traumatic brain injury risk focuses on the relationship between head impacts and the likelihood of white matter damage, often overlooking the role of neurovascular coupling in the injury response. To fill this gap, we combined biomechanical and neurodynamic principles to simulate alterations to large-scale resting-state brain activity following head impacts. We simulated cortical neural activity with a network of Kuramoto phase oscillators, using structural connectivity to define coupling and a vascular-informed local resource term to capture neurovascular coupling. By combining the neurodynamic model with a brain mechanics model, we investigated two mechanistic pathways of network dysfunction: (1) white matter damage, reflected in degrading network edges, and (2) local tissue oxygenation decline, reflected in adjusting the resource term at each network node. We simulated 53 real-world head impacts using a vasculature template to evaluate the changes in simulated functional connectivity (FC) and neural dynamics relative to injury outcomes (concussion vs. no concussion). To assess vascular variability, simulations were repeated across 41 individual vasculature maps. Our results show simulated FC changes (measured by Pearson’s correlation) consistently correlated well with injury outcomes, regardless of injury mechanism (AUC = 0.89 and 0.90), However, the two injury models yielded distinct FC patterns as indicated by graph metrics. Vascular variability substantially influenced how injury affected FC, with some brains exhibiting resilience to synchrony disruption depending on their vascular structure. These findings offer testable insight into the neurovascular mechanism of brain dysfunction after TBI and have important implications for individualized protection and treatment.